Nasionalisme Qurani dan Relevansinya dengan Semangat Kebangsaan Indonesia: Studi QS. [49]: 13, QS. [89]: 8 dan QS. [2]: 143 - lufaefi Ptiq (LP2M IAIN Palangka Raya, 2019)
In the modern era, it emerges a movement wanting to reject the concept of nationalism and replace it with the idea of islamic khilāfah, since nationalism only makes humans become worse. The spirit of life is based solely on competition of hatred and evil (xenophobia). This is caused by reality, since the growing nationalism is not based on the Qur’an, but it only inherits the West. With textual and contextual analysis of the verses of nationalism, this paper presented nationalism in the perspective of Qur’an through verses about the state and nation. This paper wants to examine how nationalism is desired by Qur’an and how relevant it is to the nationalism of Indonesian people. The result, the nationalism desired by Qur’an is a spirit of nationality, not nationalism based on pride. Quranic nationalism makes the nation compete with other nations in the world in achieving common goals. This is relevant to the spirit of Indonesian nationalism, at least there are three principles matching it, namely unity, justice and prosperity.